Understanding the Man and His Times, Discussing Life Through the Lens of Death: A Review of “A Trace of Humanity” - YANG, Lin (Journal of Research for Christianity in China (JRCC), 2022)
Ye Nong and Shao Jian, Traces of Humanity: Rubbings of Tombstones from the Graves of Jesuit Missionaries in Shanghai, Held in the Archives of the French Jesuit Society, Guangzhou: Jinan University Macau Research Institute; Macau: Macau Foundation; Shanghai: Institute of History, Shanghai Academy of Social Sciences, August 2020. 16mo format, 176,000 characters, black-and-white illustrations, Price: 180 Australian dollars.